How electoral competition shapes local public goods provision in South Africa. Issue 2 (17th February 2022) - Zimbalist, Zack
ABSTRACT: This article aims to explain stark local-level inequalities in public goods access in South Africa and put forth a new framework as to how local electoral competitiveness and accountability influence public service delivery. Drawing on quantitative and qualitative data, the article shows that local electoral competitiveness (or ruling party dominance) drives variation in accountability and public goods provision at the local level. In competitive municipalities, South Africa's robust fully decentralized democracy and independent media, along with institutionalized accountability mechanisms, allow citizens, dissenting ruling party members, and opposition figures to exert positive pressures on public goods delivery. By contrast, in municipalities dominated by the ruling party, accountability mechanisms are less likely to be effectively utilized and local governments face less pressure to deliver some of the goods that citizens need most—water, sanitation, and refuse removal.